2011
DOI: 10.1038/ajg.2011.82
|View full text |Cite
|
Sign up to set email alerts
|

Importance of Host Genetic Factors HLA and IL28B as Predictors of Response to Pegylated Interferon and Ribavirin

Abstract: The HLA-DQB1*0301 allele and IL28B genotype are factors that are associated independently with SVR. There is a synergism between the HLA-DQB1*0301 and HLA-A*0201 alleles with polymorphism rs12979860 CC, which increases the SVR rate. IL28B genotype is the best predictor of SVR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 31 publications
1
20
0
Order By: Relevance
“…These mothers were characterized by low viral load and by the absence of any increase in ALT levels after delivery. These findings are in accordance with those of previous studies, which have identified the main risk factors for perinatal mother-to-child transmission of HCV as the high concentration of HCV-RNA in maternal blood and HIV co-infection [25]. Two studies have shown that high ALT levels in the serum during pregnancy and at delivery are associated with higher rates of HCV-VT [42], [43].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…These mothers were characterized by low viral load and by the absence of any increase in ALT levels after delivery. These findings are in accordance with those of previous studies, which have identified the main risk factors for perinatal mother-to-child transmission of HCV as the high concentration of HCV-RNA in maternal blood and HIV co-infection [25]. Two studies have shown that high ALT levels in the serum during pregnancy and at delivery are associated with higher rates of HCV-VT [42], [43].…”
Section: Discussionsupporting
confidence: 92%
“…Rs12979860 genotyping was performed by means of a Taqman 5′ allelic discrimination assay (Custom Assay Service, Applied Biosystems, Foster City, CA, USA) as described previously [24], [25].…”
Section: Methodsmentioning
confidence: 99%
“…This variant is near the IL28B loci, which encodes type III IFN-k3 [14]. In a previous study, we showed that the HLA-DQB1 ⁄ 0301 allele and the IL28B polymorphisms rs12979860 are significant independent predictors of response to pegIFN-a/RBV in patients with CHC [15].…”
Section: Introductionmentioning
confidence: 98%
“…However, Chinese patients with DRB1*07 allele presented almost complete response to treatment, while DRB1*04 is associated with no responsiveness [19]. Another study showed that HLA-DQB1*0301 allele is associated with SVR; also there is a synergism between the HLA-DQB1*0301 and HLA-A*0201 alleles increasing the SVR rate [20]. Finally in a recent Egyptian study, HLA DRB1*01, DQB1*03, and DQB1*05 alleles were associated with viral clearance, while DRB1*7 and DQB1*02 alleles were associated with viral persistence [21].…”
Section: Introductionmentioning
confidence: 99%